Penanaman Seribu Pohon Sebagai Upaya Mencegah Banjir dan Tanah Longsor di Desa Eyat Mayang, Lembar, Nusa Tenggara Barat - Prapti Sedijani; Miko Eniarti; Nurwidianti; Siska Yulia Hermana; Jumriani (Universitas Mataram, 2022)
Eyat Mayang is a hilly Village where landslides can occur during heavy rains. The rainfall makes the dike unable to accommodate the overflow from the river. This condition is exacerbated by the unavailability of a Garbage Final Destination (TPA), causing the community to throw their garbage in the river. In addition, silting of the river naturally occurs. Garbage piling and river siltation are the main causes for flooding. Based on data, in 2021 there were 2 floods that resulted in damage to infrastructure, housing, and public facilities, which caused substantial material losses beside the immaterial things. There were 785 families that were impacted by floods in 2021. Therefore, Students of Mataram University (UNRAM) who were conducting Integrated Community Service in the area Period of 2021/2022 carry out programs, one of which was called